2017
DOI: 10.1101/147223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial sampling in human visual cortex is modulated by both spatial and feature-based attention

Abstract: Spatial attention changes the sampling of visual space. Behavioral studies suggest that feature-based attention modulates this resampling to optimize the attended feature’s sampling. We investigate this hypothesis by estimating spatial sampling in visual cortex while independently varying both feature-based and spatial attention.Our results show that spatial and feature-based attention interacted: resampling of visual space depended on both the attended location and feature (color vs. temporal frequency). This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 124 publications
(178 reference statements)
0
9
2
Order By: Relevance
“…Most approaches investigated the top-down modulation of spatial visual attention modeled as an attentional gain field (Kay, Weiner, & Grill-Spector, 2015;Klein, Harvey, & Dumoulin, 2014). The observations were changes in receptive field positions toward the attended location (Klein et al, 2014;Vo, Sprague, & Serences, 2017) as well as an increase in pRF size (Kay et al, 2015;Sheremata & Silver, 2015;van Es, Theeuwes, & Knapen, 2018). However, these changes were absent in early visual areas (Kay et al, 2015;Vo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most approaches investigated the top-down modulation of spatial visual attention modeled as an attentional gain field (Kay, Weiner, & Grill-Spector, 2015;Klein, Harvey, & Dumoulin, 2014). The observations were changes in receptive field positions toward the attended location (Klein et al, 2014;Vo, Sprague, & Serences, 2017) as well as an increase in pRF size (Kay et al, 2015;Sheremata & Silver, 2015;van Es, Theeuwes, & Knapen, 2018). However, these changes were absent in early visual areas (Kay et al, 2015;Vo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of Gabors that was assigned either colour combination was manipulated by a 3-up-1-down staircase procedure to ensure 79% correct separately for 4 different stimulus eccentricities. Attention to the bar ensures elevated BOLD responses [24], and this task furthermore ensures equal attentional load regardless of stimulus location [25]. A white circular fixation circle at 0.15 degrees of visual angle in diameter was present at the centre of the screen at all times.…”
Section: Individual Participant Datamentioning
confidence: 99%
“…Previous studies have found that attention can modulate the responses in the attended location (Kastner, De Weerd, Desimone, & Ungerleider, 1998;Murray & Wojciulik, 2004;O'Craven, Downing, & Kanwisher, 1999;Wojciulik, Kanwisher, & Driver, 1998). Attention can also have an influence in both the pRF size and position estimates (Klein et al, 2014;van Es, Theeuwes, & Knapen, 2018). However, we don't think that the pRF sizes observed in our results are influenced by an attention towards the stimuli.…”
Section: Discussioncontrasting
confidence: 85%
“…Similarly, attention affects pRF properties, such as pRF position and size (Klein et al, 2014;van Es et al, 2018). PRF position changes due to attention increases up the visual hierarchy.…”
Section: Discussionmentioning
confidence: 99%